2‐Periodic self‐dual tilings. Issue 1 (16th November 2016) - Delgado-Friedrichs, Olaf; O'Keeffe, Michael
Abstract : All uninodal, binodal and trinodal 2‐periodic self‐dual tilings are enumerated and described. Abstract : 2‐Periodic self‐dual tilings are important in fields ranging from crystal chemistry to mathematical physics. They have been systematically enumerated using combinatorial tiling theory, and 1, 5 and 62 uninodal, binodal and trinodal self‐dual tilings have been found. This paper illustrates all uninodal and binodal self‐dual tilings and selected trinodal self‐dual tilings. Most of these structures are described for the first time.